European Fiscal Governance and Cyclical Stabilisation: Searching for a Lasting Arrangement - Nicolas Carnot (Intereconomics, 2017)
Starting from a brief assessment of the present rules-based framework in this respect, this piece stresses that the possible addition of a common stabilisation capacity has to be considered in deep connection with (possibly revised) fiscal rules.
Keywords: 330